PENGARUH BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN KUTAI TIMUR - Imam Nazarudin Latif, Desi Rosiana Sari, LCA. Robin Jonathan, (EKONOMIA, 2016)
The aims of this research is to acknowledge the positive influence between work culture and staff performance of Kesbang Politics of East Kutai Regency. The analysis instrument used is simple regression assessment. The samples collected by using questionnaire method for 45 staffs of Kesbang Politics of East Kutai Regency.The result of simple regression analysis between work culture and staff performance variable is that the equation of Y = 0,286+ 0,256 X. Meanwhile, r correlation is 0,404 after being compared to r table where N = 45 with significance level 5% resuls the empiric calculation is r tabel 0,404> 0,245. Therefore, work hypothesis (Ha) is trully accepted and rejects hypothesisnull (Ho). There is positive and significant influence between work culture and staff performance of Kesbang Politics of East Kutai Regency.